GAMBARAN KONSEP DIRI LAKI-LAKI SEKS DENGAN LAKI-LAKI (LSL) DI KOTA MATARAM - Maria Yosevina Agata; Dinar Saurmauli Lubis; Pande Putu Januraga; I Made Eka Santosa; Ni Made Sumartyawati (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: Men who have sex with men (MSM) in Mataram City face various challenges related to self-acceptance and social environment. Some of them have a negative self-concept characterized by a lack of confidence in expressing their identity due to fear of rejection from family and society, which still considers homosexuality to be against social norms. This situation often affects their behavior, such as limiting social interactions and hiding their identity. Meanwhile, MSM with positive self-concept tend to be more self-confident and able to accept themselves, even though they still face social stigma. This self-concept overview of LSM is important to understand as a first step in supporting them towards psychological and social well-being. Objective: to find out the description of the self-concept of LSL in the city of Mataram. Method: This research is a quantitative descriptive research. The research population was registered MSM living in Mataram City with a sample size of 154 MSM. Sample selection uses systematic random sampling technique. The research was conducted by providing a self-concept questionnaire and the analysis used was univariate analysis using frequency distribution. Result: All components of self-concept including self-identity, self-image, self-esteem, self-ideal and self-role of the respondents are positive. Conclusion: The self-concept of LSL in Mataram city is positive.